Pengaruh Etos Kerja, Sikap Kerja, Loyalitas Kerja Dan Motivasi Kerja Terhadap Efektivitas Kerja Karyawan PT. Laras Era Perdana Batam - Ilham Hakim; Amri Sanjaya; Hendri Herman (LPPM Universitas Jambi, 2022)
The purpose of this study is to find out the influence of work ethic, work attitude, work loyalty and work motivation on work effectiveness. The object of this research is PT Laras Era Perdana Batam. The sample used in the study was 85 respondents. Data obtained by distributing questionnaires to respondents to be processed using the SPSS application. The results of this study are partially work ethic has a significant effect on work effectiveness, work attitudes have a significant effect on work effectiveness, work loyalty has a significant effect on work effectiveness, work motivation affects work effectiveness and simultaneously work ethic, work attitude, work loyalty and work motivation have a significant effect on work effectiveness. The R square value of 33.6% means that work ethic, work attitude, work loyalty, and work motivation can affect work effectiveness by 33.6%, while the remaining 66.4% is influenced by other factors not studied in the study.